Integration of Bio-Enzyme-Treated Super-Wood and AIE-Based Nonwoven Fabric for Efficient Evaporating the Wastewater with High Concentration of Ammonia Nitrogen - Ding, Qian; Jin, Bingqi; Zheng, Yinxia; Zhao, Huiru; Wang, Jun; Li, Haoxuan; Wang, Dong; Tang, Ben Zhong (Nano-Micro Letters, 2025)
The treatment of ammonia nitrogen wastewater (ANW) has garnered significant attention due to the ecology, and even biology is under increasing threat from over discharge ANW. Conventional ANW treatment methods often encounter challenges such as complex processes, high costs and secondary pollution. Considerable progress has been made in employing solar-induced evaporators for wastewater treatment. However, there remain notable barriers to transitioning from fundamental research to practical applications, including insufficient evaporation rates and inadequate resistance to biofouling. Herein, we propose a novel evaporator, which comprises a bio-enzyme-treated wood aerogel that serves as water pumping and storage layer, a cost-effective multi-walled carbon nanotubes coated hydrophobic/hydrophilic fibrous nonwoven mat functioning as photothermal evaporation layer, and aggregation-induced emission (AIE) molecules incorporated as anti-biofouling agent. The resultant bioinspired evaporator demonstrates a high evaporation rate of 12.83 kg m−2 h−1 when treating simulated ANW containing 30 wt% NH4Cl under 1.0 sun of illumination. AIE-doped evaporator exhibits remarkable photodynamic antibacterial activity against mildew and bacteria, ensuring outstanding resistance to biofouling over extended periods of wastewater treatment. When enhanced by natural wind under 1.0 sun irradiation, the evaporator achieves an impressive evaporation rate exceeding 20 kg m−2 h−1. This advancement represents a promising and viable approach for the effective removal of ammonia nitrogen wastewater. Highlights: 1 Bio-enzyme-treated super-wood and aggregation-induced emission (AIE)-based nonwoven fabric is integrated into a solar evaporator. 2 The evaporator demonstrates a high evaporation rate of 12.83 kg m−2 h−1 when treating simulated wastewater containing 30 wt% NH4Cl under 1.0 sun of illumination. 3 AIE-doped evaporator exhibits remarkable photodynamic antibacterial activity against mildew and bacteria.